Project governance mechanisms and the performance of software development projects: Moderating role of requirements risk. Issue 4 (May 2019) - Haq, Saif Ul; Gu, Dongxiao; Liang, Changyong; Abdullah, Iqra
Abstract: Over the years, practitioners and academicians have been perplexed by low efficiency and poor performance in IT projects. Previous studies have uncovered a variety of critical factors, including effective project governance mechanisms that can trigger project performance and curb opportunism. However, an obvious question that emerges is how effective these governance mechanisms are at improving the performance of an IT organization and software development project in the presence of risk factors. Hence, the overarching objective of the current study is the development of a moderation model to investigate the effectiveness of these governance mechanisms in the presence of requirements risk. This paper follows a positivist research philosophy where a quantitative deductive approach has been used to collect the data of 318 respondents from 175 software development firms based in Pakistan. Statistical Package for the Social Sciences (SPSS) and Structural Equation Modeling (SEM) through SmartPLS 3 have been used to analyze the hypotheses. The results of the study indicate that contractual and relational governances significantly influence project performance and are useful in reducing opportunism. Moreover, there is evidence that the presence of requirements risk tends to negatively moderate the influence of contractual and relational governances on project performance. The findings will help not only Pakistan's software firms, but also those in developing countries that want to improve performance through effective project governance and risk management. Highlights: Contractual governance and relational governance are useful to enhance the performance of software development projects. The requirements risk moderates the relationship between project governance mechanisms and project performance. Opportunism doesn't have direct effects on project performance for the sampled firms.